Cover Feature: Heat Shock Proteins Revisited: Using a Mutasynthetically Generated Reblastatin Library to Compare the Inhibition of Human and Leishmania Hsp90s (ChemBioChem 6/2018). (5th March 2018) - Mohammadi‐Ostad‐Kalayeh, Sona; Stahl, Frank; Scheper, Thomas; Kock, Klaus; Herrmann, Christian; Heleno Batista, Fernanda Aparecida; Borges, Júlio César; Sasse, Florenz; Eichner, Simone; Ongouta, Jekaterina; Zeilinger, Carsten; Kirschning, Andreas
Abstract : The cover feature picture shows new reblastatin derivatives obtained by a chemo‐biosemisynthetic approach with the corresponding aminobenzoic acid derivatives as starting building blocks. The fluoro and amino derivatives exerted high inhibitory activity on human and leishmania Hsp90, whereas the presence of an alkynyl substituent leads to selective activity towards Hsp90 from leishmania. The inhibitory activity was unraveled by using a novel protein microarray system with purified Hsp90 proteins and was further confirmed by cell‐based assays and ITC measurements. More information can be found in the full paper by C. Zeilinger, A. Kirschning et al. onpage 562 in Issue 6, 2018 (DOI:10.1002/cbic.201700616 ).